Dem Herkules zu Füssen III. : Elenea Carvajal - Stefan Fedeler - Martin Hast - Berthold Hörbelt - Wolfgang Winter - Stefan Hunstein - Barbara Jung - Martina Klein. Debüt: Tobias Brembeck, Olaf König, Eva Millauer, Andrea Nagel, Jens Nippert, Judith Nopper. - Witzmann, Pia (Kassel : Museum Fridericianum, 1995)
Carvajal, Elena ; Fedeler, Stefan ; Hast, Martin ; Hörbelt, Berthold ; Winter, Wolfgang ; Hunstein, Stefan ; Jung, Barbara ; Klein, Martina ; Brembeck, Tobias ; König, Olaf ; Millauer, Eva ; Nagel, Andrea ; Nippert, Jens ; Nopper, Judith
biografie
Duits
Dem Herkules zu Füssen III, Museum Fridericianum, Kassel, 10.9. - 29.10.1995
boek
Keywords: Kassel